Representation of women in Buya Hamka's novel by A. Fuadi - Khaerunnisa, Khaerunnisa; Mutiarani, Mutiarani; Devi , Wika Soviana; Arumdapta, Rananda; Nuryani, Rina (Universitas Ahmad Dahlan, 2024)
A Literary works and social realities that occur in the social environment of society are inseparably linked. The conflicts raised can be in the form of problems experienced in everyday life. One of the conflicts that often occurs and is discussed in a literary work is about feminism. This research aims to find the image of women in Siti Raham contained in the novel Buya Hamka by A. Faudi. The figure of Siti Raham who is the wife of Buya Hamka is the subject of discussion in this study. The research method used is a qualitative method that is descriptive of the observed object. The data source used in this research is the novel Buya Hamka by A. Faudi. The feminist approach is used to analyze the image of female characters based on the physical, psychological, and social aspects of the story. The results of this research show that from various categories, it can be concluded that Siti Raham is a great woman and is successful as a child, wife, mother and in the social environment of society. She was able to raise 10 children, even when her husband was away from them.